2005
DOI: 10.1037/h0087264
|View full text |Cite
|
Sign up to set email alerts
|

Promoting forgiveness among co-workers following a workplace transgression: The effects of social motivation training.

Abstract: Forgiveness is one construct that is beginning to demonstrate promise as a health and relationship promoter within the workplace. The primary aim of this research was to examine the effects of one psychological intervention (social motivational training) that was developed to promote forgiveness among co-workers. In the first of two studies, workers were randomly assigned to one of two intervention conditions (i.e., job satisfaction training, social motivational training). Participants read a vignette in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Oftentimes, these behaviors were attributed to something external to the people manifesting it, therefore not causing a detrimental mark on the relationship. The theme is congruent with recent findings in the area of health psychology where individuals' responses to negative events have significant implications to their wellbeing (Ward Struthers, Dupuis, & Eaton, 2005). One response to restore positive feelings is by choosing to see what is positive about the situation as well as changing one's perspectives.…”
Section: Using the Positive Feeling To Counter Snlsupporting
confidence: 74%
See 1 more Smart Citation
“…Oftentimes, these behaviors were attributed to something external to the people manifesting it, therefore not causing a detrimental mark on the relationship. The theme is congruent with recent findings in the area of health psychology where individuals' responses to negative events have significant implications to their wellbeing (Ward Struthers, Dupuis, & Eaton, 2005). One response to restore positive feelings is by choosing to see what is positive about the situation as well as changing one's perspectives.…”
Section: Using the Positive Feeling To Counter Snlsupporting
confidence: 74%
“…For the employees, it was important that they are treated like family members by the higher officials of the institution influenced by trust, fairness and justice. Co-worker relationships are recognized as one of the most ubiquitous and important interpersonal relationships (Ward Struthers, Dupuis, & Eaton, 2005) and while perceived organizational support is believed to be influenced by relationships employees have in their organizations, GNL seems to be related to being accepted and treated equally by the other members of the institution. If the inner radius of colleagues and their supervisors provide a positive climate that induces positive feelings, it expands to the other offices and departments of the institution.…”
Section: Family-like Treatment Of Other Members Of the Institutionmentioning
confidence: 99%
“…ADR evolved in the USA as an option for resolving disputes outside a courtroom and in response to weaknesses in the adversarial legal system (Struthers et al, 2005). ADR methods are now practiced worldwide in various ways.…”
Section: Adrmentioning
confidence: 99%
“…Therefore, it is crucial to understand how forgiveness, ''a response… suited to improving the quality of working relations'' (Aquino et al 2003, p. 210), can be enhanced in the aftermath of workplace unfairness. Although an extensive volume of research has identified factors that can predict forgiveness (for a meta-analytic review, see Fehr et al 2010), few studies have explored how interventions can facilitate forgiveness in organizational contexts (for an exception, see Struthers et al 2005). We examine whether expressive writing can facilitate forgiveness in the workplace and explore the mechanisms underlying the relationship between expressive writing and forgiveness.…”
Section: Theoretical Backgroundmentioning
confidence: 97%